Synthesis and Characterization of Some Schiff Bases - Ibrahim, M.N.; Hamad, K.J.; Al-Joroshi, S.H. (Asian Journal of Chemistry, 2010)
A series of ten Schiff bases have been synthesized by condensation of a variety of aromatic amines with some aniline (or derivatives) and aromatic aldehyde derivatives. These Schiff bases have been characterized by IR, 1H NMR in addition to elemental analysis.